Social entrepreneurship as sustainability agency - Lehtimäki, Hanna (Edward Elgar Publishing, 2021)
In this review, we develop the idea of social entrepreneurship as sustainability agency. We review literature on social entrepreneurship and examine what it means as a contested concept and hybrid logic, how it implicates the sustainability space, and how that makes the social entrepreneur a change agent in sustainable economy. As a result, we articulate social entrepreneurship as a sustainability agency where the social entrepreneurs balance not only the hybrid organizing of social and economic value creation, but also the creation of environmental value so as to become sustainable enterprises. In this way, they transform themselves as well as the very context in which they are embedded. The purpose of our review is to open the past and present research on what role social entrepreneurship plays in sustainability agency, and what that offers in terms of future research directions.